Emissivity and electrooptical properties of semiconducting quantum dots/rods and liquid crystal composites: a review. (18th April 2016) - Singh, Gautam; Fisch, Michael; Kumar, Satyendra
Abstract: Investigations of the mixtures of semiconducting quantum scale particles in anisotropic liquid crystal (LC) medium have become a vibrant area of research primarily due to their very interesting phenomenology. The results of these investigations fall into four groups: (i) Photoluminescent emissive properties of the quantum particles ordinarily depend on the size, shape, and chemical nature of the particles. These undergo important changes in their spectrum, polarization, and isotropy of emission when dissolved in an anisotropic LC phase. Moreover, their response to external stimuli such as mechanical, optical, or electric fields is altered in important ways; (ii) physical properties of LCs such as viscosity, dielectric relaxation, etc are modified by the addition of quantum particles. Their presence in ferroelectric smectic LC is known to give rise to an antiferro- to ferri-electric phase transition and suppresses the paraelectric phase; (iii) switching characteristics of LC devices are altered in important ways by the addition of quantum particles. Their threshold voltage is usually lowered, contrast ratio, and switching speed of nematic, ferroelectric, and cholesteric devices may increase or decrease depending on the concentration, applied field, and particle anisotropy; and (iv) controlled aggregation of quantum particles at the interface between isotropic and LC domains, near added polystyrene beads, and in the vicinity of point defects gives rise to interesting photonic structures, enables studies of photon antibunching and single photon sources. Clearly, there is a need to understand the basic and applied aspects of these systems and find routes to their technological applications including sensors, electrooptical devices, and solar energy harvesting. This review provides an overview of recent work involving liquid crystals and a variety of quantum particles.